Influence of ultrasound therapy on volume of the synovial fluid in knee joint arthrosis (gonarthrosis)-initial reports. - Beata Olesiak; Agnieszka Przedborska; Jan Wojciech Raczkowski (Kazimierz Wielki University, 2019)
SUMMARY Aim of the paper: Aim of the study was impact assessment of the ultrasonic wave on production of synovial fluid in suprapatellar pouch, pain symptoms, and knee movement range. Material and methods: The study group consisted of 23 patients that were diagnoses with excess of synovial fluid in suprapatellar pouch. The measurement of the fluid volume was made using ultrasound examination. Volume of the fluid < 4 mm is considered as positive result of the study. The data was collected with usage of a self-made study protocol. In assessment of pain symptom, the VAS scale was used. Results: Statistically significant reduction of the synovial fluid volume in suprapatellar pouch (p